Pengaruh Online Consumer Reviews Pada Aplikasi Female Daily Network terhadap Keputusan Pembelian Produk Skincare Somethinc - Jessica Trivena; Rezi Erdiansyah (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
The beauty industry is one industry that is quite concerned with online customer reviews. Beauty products are product categories that are assessed through personal information experiences. Evaluation of the experience of using the product becomes important for consumers of beauty products. The purpose of this study was to determine the extent of the impact and influence of online consumer reviews on purchasing decisions for SomeThinc Skincare products. The theory that the author uses is Social Judgment Theory, this theory describes how a person makes judgments based on the relevance of the information received and related. Explanative quantitative research using questionnaire data collection method which was distributed to 105 respondents who read SomeThinc product reviews on the Female Daily Network application through Purposive Sampling. Then the data obtained will be analyzed using the Simple Linear Regression Test. The results of this study indicate that the Online Consumer Review on the Female Daily Network application has an effect on purchasing decisions for SomeThinc products by 58.2% so it can be concluded that the Online Consumer Review is in the Latitude of Acceptance category from Social Judgment Theory. Therefore, based on the results of the research that the researchers did, the researchers gave advice to SomeThinc to develop reviews on the Female Daily application to be the right marketing strategy in the future. Industri kecantikan merupakan salah satu industri yang cukup mementingkan online customer reviews. Produk kecantikan merupakan kategori produk yang dinilai melalui pengalaman informasi pribadi. Evaluasi pengalaman penggunaan produk menjadi penting bagi konsumen produk kecantikan. Tujuan penelitian ini untuk mengetahui sejauh mana dampak dan pengaruh review konsumen online terhadap keputusan pembelian beberapa produk Skincare Somethinc. Teori yang penulis gunakan adalah Social Judgement Theory, teori ini menggambarkan bagaimana seseorang membuat penilaian berdasarkan relevansi informasi yang diterima dan terkait. Penelitian bersifat kuantitatif eksplanatif menggunakan metode pengumpulan data kuesioner yang dibagikan terhadap 105 responden yang membaca review produk Somethinc pada aplikasi Female Daily Network melalui Purposive Sampling. Kemudian data-data yang didapat akan dianalisis menggunakan Uji Regresi Linear Sederhana. Hasil penelitian ini menunjukkan bahwa Online Consumer Review pada aplikasi Female Daily Network berpengaruh terhadap keputusan pembelian produk Somethinc sebesar 58,2% sehingga dapat disimpulkan bahwa Online Consumer Review di dalam kategori Latitude of Acceptance dari Social Judgement Theory. Maka dari itu, berdasarkan hasil penelitian yang peneliti lakukan, peneliti memberi saran terhadap Somethinc untuk mengembangkan ulasan pada aplikasi Female Daily menjadi strategi pemasaran yang tepat kedepannya.